2015
DOI: 10.1590/0074-02760140386
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Trypanosoma cruzi-specific T-cell responses after chemotherapy for chronic Chagas disease

Abstract: The aim of this review is to describe the contributions of the knowledge of T-cell responses to the understanding of the physiopathology and the responsiveness to etiological treatment during the chronic phase of Chagas disease. T-helper (Th)1 and interleukin (IL)-10 Trypanosoma cruzi-specific T-cells have been linked to the asymptomatic phase or to severe clinical forms of the disease, respectively or vice versa, depending on the T. cruzi antigen source, the patient’s location and the performed immunological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
1
15
1
Order By: Relevance
“…A higher prevalence of IFN-γ + IL-2 + responders as well as a higher magnitude of these responses was found in SD individuals than in SP subjects. These findings are at odds with the low frequency of IL-2-producing T-cells in documented SP adult subjects (e.g., positive on all serological tests) observed herein, and in our previous studies ( 25 , 33 ).…”
Section: Discussioncontrasting
confidence: 98%
“…A higher prevalence of IFN-γ + IL-2 + responders as well as a higher magnitude of these responses was found in SD individuals than in SP subjects. These findings are at odds with the low frequency of IL-2-producing T-cells in documented SP adult subjects (e.g., positive on all serological tests) observed herein, and in our previous studies ( 25 , 33 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Increased antigen-specific IFN-␥ significantly correlated with reduced parasitemia, and increased antigen-specific IL-4 correlated with reduced parasitemia and cardiac parasite burdens. Absence of parasitemia and parasite-specific immune responses have been used as indicators of drug efficacy in humans (19,26), and our data show that these parameters serve as informative correlates of protection in our combination treatment model as well. Limitations of this model were observed.…”
Section: Figmentioning
confidence: 62%
“…Studies in chronic indeterminate human patients without disease and chronic patients with disease have confirmed that antigen-specific IFN-␥ balanced by IL-10 correlates with the absence of clinical disease (25). When parasite-specific immune responses are evaluated after benznidazole treatment, antigen-specific IFN-␥ is initially increased and is believed to enhance efficacy of the drug (26,27). Further studies in preclinical models show that benznidazole cure rates are significantly reduced in mice lacking IFN-␥, IL-12, and tumor necrosis factor alpha (TNF-␣) (28).…”
mentioning
confidence: 99%
“…Research to date has also hypothesized that the quality of T-cell responses and immune-regulatory mechanisms might determine the pattern of cellular responses and the severity of disease in chronic T. cruzi infection. The quality of T-cell responses might be a key factor, not only in disease evolution but also in chemotherapy responsiveness [137]. This may also explain the differing response rate to anti-parasitic treatment among children in comparison with adults, as children have a T-cell profile associated with a more robust clinical response [138].…”
Section: Why Are There Poor Cure Rates In Chronic Patients?mentioning
confidence: 99%